The Effect of Nonsteroidal Anti-Inflammatory Drugs on Union Rates Following Operative Repair of Distal Radius Fractures - Michael Chang, MD; Alexis Kasper, BS; Juliet Chung, MD; Justin Wright, BS; Margaret Pennington, MD; Asif M. Ilyas, MD, MBA (Journal of Hand Surgery Global Online)
Purpose: Multimodal pain regimens for controlling postoperative pain after surgery for fractures often include nonsteroidal anti-inflammatory drugs (NSAIDs). However, some surgeons remain reluctant toward prescribing NSAIDs because of concerns of compromised bone healing. The study hypothesis was that a short-term prescription of NSAIDs for postoperative pain after distal radius fracture repair would not result in a significant difference in union rates. Methods: Consecutive patients who underwent surgical repair of a distal radius fracture with a volar locking plate from a single academic institution with five hand surgery fellowship-trained orthopedic surgeons were retrospectively reviewed. The cohort was divided into those prescribed +NSAIDs and those who were not (-NSAIDs) postoperatively. Preoperative patient characteristics and postoperative pain regimens were recorded. Comparisons between the two groups were made based on the primary outcome being union rate and other secondary outcomes, including time to union and number of opioid tablets prescribed. Results: Four hundred and ninety-four patients were included in the final analysis, of which 115 were prescribed +NSAIDs, and 379 were not (-NSAIDs). Preoperative demographics and comorbidities were balanced between groups. A similar proportion of patients were prescribed some type of opioid. However, the +NSAIDs group was prescribed a fewer number of opioid tablets. The overall nonunion rate was 1.2%. Of these cases, two were in the +NSAIDs group, and four were in the -NSAIDs group. There was no difference in union rate between the two groups. Conclusions: The prescribing of NSAIDs after volar locking plate fixation of distal radius fractures was not associated with an increased nonunion rate in this study. This study may alleviate concerns that NSAIDs might jeopardize fracture healing when used postoperatively as part of a multimodal pain regimen following distal radius fracture repair. Type of study/level of evidence: Prognostic IV.